2020
DOI: 10.1111/jcmm.14995
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin inhibits macrophage polarization through the p‐38α/β signalling pathway and regulates OPG/RANKL balance in a mouse skull model

Abstract: Aseptic loosening caused by wear particles is a common complication after total hip arthroplasty. We investigated the effect of the quercetin on wear particle‐mediated macrophage polarization, inflammatory response and osteolysis. In vitro, we verified that Ti particles promoted the differentiation of RAW264.7 cells into M1 macrophages through p‐38α/β signalling pathway by using flow cytometry, immunofluorescence assay and small interfering p‐38α/β RNA. We used enzyme‐linked immunosorbent assays to confirm tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Quercetin at 50 or 100 mg/kg per day inhibited titanium-particle-induced osteolysis by increasing bone area and decreasing osteoclast formation in vivo [ 45 ]. In another study, female C57BL/6 mice with titanium-particle-induced osteolysis and treated with quercetin (2 or 5 mg/kg/day) for 14 days had higher BV/TV but lower total porosity, erosion area and osteoclast number [ 46 ].…”
Section: In Vivo Evidence On the Effects Of Quercetin On Bonementioning
confidence: 99%
See 3 more Smart Citations
“…Quercetin at 50 or 100 mg/kg per day inhibited titanium-particle-induced osteolysis by increasing bone area and decreasing osteoclast formation in vivo [ 45 ]. In another study, female C57BL/6 mice with titanium-particle-induced osteolysis and treated with quercetin (2 or 5 mg/kg/day) for 14 days had higher BV/TV but lower total porosity, erosion area and osteoclast number [ 46 ].…”
Section: In Vivo Evidence On the Effects Of Quercetin On Bonementioning
confidence: 99%
“…Numerous studies have found that quercetin inhibits the formation of osteoclast-like cells (evidenced by TRAP-positive multinucleated cells), bone resorption pit and F-actin ring formation in RAW264.7 cells, human peripheral-blood mononuclear cells (PBMCs) or bone-marrow macrophages treated with macrophage colony-stimulating factor (M-CSF) and/or RANKL [ 31 , 32 , 45 , 46 , 68 , 74 , 94 , 95 , 96 ]. In another study using highly purified rabbit osteoclasts, treatment with 50 μM quercetin caused a reduction in the total area of resorption pit [ 97 ].…”
Section: In Vitro Evidence Of the Effects Of Quercetin On Bone Celmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, the increase in bacterial number is related to a reduction of innate and adaptative immunity; on the other hand, the growth of drug-resistant bacterial strains makes the treatment of these diseases a challenge. In light In recent years, the focus on this compound has increased due to its several therapeutic properties, such as anti-inflammatory [13][14][15], antioxidant [16], anti-tumoral [17], anti-ulcer [18], anti-allergy [19], anti-diabetic [20], antihypertensive [21], immunomodulatory [22], and gastroprotective [23] activities. Moreover, the proven antiviral [24] activity has suggested its administration in the prevention and treatment of SARS-CoV-2-related disease [25].…”
Section: The Antibacterial Effect Of Quercetinmentioning
confidence: 99%